Description of a new species of Hobbsinella (Crustacea, Bathynellacea, Bathynellidae) from Colorado (USA) based on morphological and molecular characters - Camacho, Ana Isabel; Mas-Peinado, Paloma; Bonwell, Carly B.; Mcdonald, Jenna N.; Dorda, Beatriz A.; Rey, Isabel; Taylor, Steven J. (European Journal of Taxonomy, 2023)
A new species of Bathynellidae is described from Colorado (USA). Hobbsinella gunnisonensis Camacho & Taylor sp. nov. displays a unique combination of morphological characters including seven-segmented antenna lacking medial seta on exopod, antennule slightly longer than antenna, three-segmented mandibular palp, four articles on endopod of thoracopods I to VII and five spines on sympod and three spines on endopod of the uropods. Partial sequences of cytochrome oxidase I (COI) and 18S have been obtained from several specimens of the new species. The mitocondrial and nuclear DNA data complement the traditional morphological taxonomic description support the validity of the new species. Molecular data for the Bathynellidae demonstrate the presence of two highly divergent genetic units, with the new species placed in the genus Hobbsinella. With the description of Hobbsinella gunnisonensis Camacho & Taylor sp. nov. and its molecular characterization, we discovered an interesting distribution of the genus, which occurs in both sides of the Continental Divide (Texas and Colorado) and different habitats.